2003
DOI: 10.1128/aac.47.5.1681-1688.2003
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Antimicrobial Susceptibility among Clinical Isolates of Pseudomonas aeruginosa and Acinetobacter baumannii from Hospitalized Patients in the United States, 1998 to 2001

Abstract: Pseudomonas aeruginosa and Acinetobacter baumannii are the most prevalent nonfermentative bacterial species isolated from clinical specimens of hospitalized patients. A surveillance study of 65 laboratories in the United States from 1998 to 2001 found >90% of isolates of P. aeruginosa from hospitalized patients to be susceptible to amikacin and piperacillin-tazobactam; 80 to 90% of isolates to be susceptible to cefepime, ceftazidime, imipenem, and meropenem; and 70 to 80% of isolates to be susceptible to cipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
184
2
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(210 citation statements)
references
References 29 publications
13
184
2
11
Order By: Relevance
“…The overall resistance rate of antimicrobials was higher in the current study than in other reports (Gunseren et al, 1999;Mendes et al, 2005;Styers et al, 2006;Patzer, Dzierzanowska, Turner, 2002;Gonlugur et al, 2004;Karlowsky et al, 2003). Moreover, the resistance rate to cephalosporins (79.5%-87.8%) was comparable to that in Iran (Hadadiet al, 2008), but higher than reported in foreign studies (Gunseren et al, 1999;Al-Lawati, Crouch, Elhag, 2000;Glupczynski et al, 2001;Patzer, Dzierzanowska,Turner, 2002;Gonlugur et al, 2004;Karlowsky et al, 2003;Meric et al, 2005).…”
Section: Discussioncontrasting
confidence: 55%
“…The overall resistance rate of antimicrobials was higher in the current study than in other reports (Gunseren et al, 1999;Mendes et al, 2005;Styers et al, 2006;Patzer, Dzierzanowska, Turner, 2002;Gonlugur et al, 2004;Karlowsky et al, 2003). Moreover, the resistance rate to cephalosporins (79.5%-87.8%) was comparable to that in Iran (Hadadiet al, 2008), but higher than reported in foreign studies (Gunseren et al, 1999;Al-Lawati, Crouch, Elhag, 2000;Glupczynski et al, 2001;Patzer, Dzierzanowska,Turner, 2002;Gonlugur et al, 2004;Karlowsky et al, 2003;Meric et al, 2005).…”
Section: Discussioncontrasting
confidence: 55%
“…The results were interpreted according to guidelines recommended by the Clinical and Laboratory Standards Institute [15]. Multi-drug-resistant (MDR) P. aeruginosa isolates were defined as resistant to at least three of the following antibiotics: Cefotaxime or cefepime, imipenem, gentamicin, or levofloxacin [16].…”
Section: Bacterial Isolation and Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…Aminoglycosides are clinically effective agents for treating infections caused by P. aeruginosa as well as other gram-negative bacilli. However, multidrug resistance is rapidly emerging in P. aeruginosa, whose spectrum of resistance often includes aminoglycosides as well as broad-spectrum ␤-lactams and fluoroquinolones (15). The most frequently encountered molecular mechanism for aminoglycoside resistance in P. aeruginosa is the production of aminoglycoside-modifying enzymes such as plasmid-dependent acetyltransferase (AAC), adenylyltransferase (AAD), and phosphotransferase (APH) (6,17,23).…”
mentioning
confidence: 99%